PEMANFAATAN E-COMMERCE BAGI GENERASI MILENIAL - Nurul Rahmadani; Masitah Handayani; Rohminatin Rohminatin; Pristiyanilicia Putri (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Abstract: The growth of the e-commerce market in Indonesia is very high and is one of the largest in the world. As a country whose population is dominated by a mid-level economy, e-commerce is very positively welcomed by the Indonesian population, especially the millennial generation. The millennial generation is a generation of young people today who are currently in the age range of 15-34 years. This generation is the biggest consumer in utilizing the internet in many ways, such as social media and e-commerce. The method used in this service is a simulation using one e-commerce application, namely Shopee. The purpose of this Community Service activity is to utilize e-commerce, especially for millennials so that they can use it in positive terms. The result of this activity was the implementation of Community Service activities attended by 30 students at SMA Negeri 2 Tanjungbalai. Keywords: e-commerce; millennial generation  Abstrak: Pertumbuhan pasar e-commerce di Indonesia sangat tinggi dan merupakan salah satu yang terbesar di dunia. Sebagai negara yang penduduknya didominasi oleh ekonomi tingkat menengah, e-commerce sangat disambut positif bagi penduduk Indonesia, terutama generasi milenial. Generasi milenial merupakan generarasi muda masa kini yang saat ini berusia dalam rentang usia15-34 tahun. Generasi ini merupakan konsumen terbesar dalam memanfaatkan internet dalam banyak hal, seperti sosial media maupun e-commerce. Metode yang digunakan dalam pengabdian ini ialah simulasi menggunakan salah satu aplikasi e-commerce, yaitu Shopee. Tujuan dilakukannya kegiatan Pengabdian Masyarakat ini adalah untuk memanfaatkan e-commerce terutama bagi generasi milenial sehingga dapat memanfaatkannya dalam hal positif. Hasil kegiatan ini ialah terlaksananya kegiatan Pengabdian Masyarakat yang dihadiri siswa-siswi SMA Negeri 2 Tanjungbalai sebanyak 30 orang. Kata kunci: e-commerce; generasi milenial